Influence of Family Socio-Economic Factors on Prevention of Premarital Sexual Behavior in Jember Regency - Iis Rahmawati; Dewi Retno Suminar; Oedoyo Soedirham ; Pingky Saptandari (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Background: the incidence of premarital sexual behavior by adolescents in the world has increased, so that adolescents need attention, guidance, supervision from parents, and good service planning related to reproductive health problems, so that teens will avoid risky behaviors namely premarital sexual behavior. Method: The cross-sectional study design was conducted on 229 adolescents aged 16-17 years with multistage random sampling. Questionnaires were used to measure family socioeconomic factors and prevention of premarital sexual behavior using theory and have been modified by researchers. The family socioeconomic factor variables include indicators of education, income, employment and number of family members and the variables for preventing premarital sexual behavior include refusing skills, increasing religiosity, avoiding pornographic media, promoting sexual health and enhancing parent-teen relations. Data analysis: using SEM using software (Analysis of Moment Structures (AMOS) version 21). Results: The effect of family socioeconomic factors on the prevention of premarital sexual behavior with a P-value of 0.849 indicates that family socio- economic factors do not significantly influence premarital sexual prevention by adolescents. Conclusion: Family factors in this case are family socio-economic factors that have no effect on premarital sexual prevention in adolescents, this can be caused by the influence of individual adolescents' attitudes and the efforts of adolescents themselves to increase their religiosity and understanding of sexual behavior healthy and responsible who ultimately can make the right decisions and be responsible for their sexual lives and have the ability to resist premarital sexual behavior.